66.0k views
5 votes
What is the solution to this system of linear equations?

y - 4x=7
2y + 4x = 2
(3,1)
(1,3)
3.-1)
(-1,3)

User Ezuk
by
5.0k points

2 Answers

1 vote

Answer:

D

Explanation:

got it right

User Giorgi Moniava
by
6.2k points
3 votes

Answer:

(- 1, 3 )

Explanation:

Given the 2 equations

y - 4x = 7 → (1)

2y + 4x = 2 → (2)

Eliminate x by adding the 2 equations term by term

(y + 2y) + (- 4x + 4x) = (7 + 2), that is

3y = 9 ( divide both sides by 3 )

y = 3

Substitute y = 3 in either of the 2 equations and solve for x

Using (2), then

(2 × 3) + 4x = 2

6 + 4x = 2 ( subtract 6 from both sides )

4x = - 4 ( divide both sides by 4 )

x = - 1

Solution is (- 1, 3 )

User Paul Losev
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.